The Pengembangan Media Pembelajaran CPS (Colligative Properties Of The Solution) Berbasis Intelligen Tutoring System untuk Meningkatkan HOTS Mahasiswa Pendidikan IPA: Pengembangan Media Pembelajaran CPS (Colligative Properties Of The Solution) Berbasis Intelligen Tutoring System untuk Meningkatkan HOTS Mahasiswa Pendidikan IPA - Mellyta Uliyandari; Nirwana Nirwana; Sutarno Sutarno (UNIB Press, 2023)
This research aimed to develop CPS learning media based on the Intelligent Tutoring System to improve the HOTS abilities of Science Education Students, especially on the Colligative Properties of Solutions material. The method used in this research was research and development with 4D method, namely define, design, develop and disseminate. In the definition stage, learning objectives were formulated. The design stage was carried out by designing learning media, while at the development stage, learning media were validated by media experts and material experts, the dissemination stage was carried out via YouTube and Unib e-learning. The results of the research show that the learning media validation scores by material experts and media experts were at 73 and 55 in the